The Influence of Culture in Character Design in Open World Games in terms of Roland Barthes' Visual Semiotic Theory - Gloria Chrsitiana Damayanti (Faculty Of Arts and Design Sebelas Maret University, 2023)
The emergence of identification, way of life, and norms that apply to society are interrelated and formed by the existence of culture. Culture that carries these three things coexists with humans and becomes an important aspect of life. Open World Game is a game that invites players to create a player-made world. By creating a culture, Open World Game raises a culture that exists in the world to create and shape the identity of its characters. One of them is Genshin Impact. Genshin Impact raises several cultures in the world, one of which is Sumeru which elevates Middle Eastern culture. Through the Semiotic Theory put forward by Roland Barthes, the author analyzes the role and application of this culture to the visual characters in the Genshin Impact Open World Game.   Keywords: Visual Analysis, Open World Game, Graphic Design, Design Critique